2021
DOI: 10.1002/hep.31906
|View full text |Cite
|
Sign up to set email alerts
|

T‐Cell Immunoglobulin and Mucin Domain‐Containing Protein‐4 Is Critical for Kupffer Cell Homeostatic Function in the Activation and Resolution of Liver Ischemia Reperfusion Injury

Abstract: Background and Aims Liver ischemia reperfusion injury (IRI) remains an unresolved clinical problem. This study dissected roles of liver‐resident macrophage Kupffer cells (KCs), with a functional focus on efferocytosis receptor T‐cell immunoglobulin and mucin domain‐containing protein‐4 (TIM‐4), in both the activation and resolution of IRI in a murine liver partial warm ischemia model. Approach and Results Fluorescence‐activated cell sorting results showed that TIM‐4 was expressed exclusively by KCs, but not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Kupffer cells are liver-resident macrophages associated with proinflammatory reactions, ischemia-reperfusion, and immune reactions. 14 , 15 MARCO is typically expressed on restricted subpopulations of macrophages in peripheral immune organs. 16 We verified that MARCO expression was predominantly localized to Kupffer cells in HCC tissues, as determined by the colocalization of MARCO and CD68 using immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Kupffer cells are liver-resident macrophages associated with proinflammatory reactions, ischemia-reperfusion, and immune reactions. 14 , 15 MARCO is typically expressed on restricted subpopulations of macrophages in peripheral immune organs. 16 We verified that MARCO expression was predominantly localized to Kupffer cells in HCC tissues, as determined by the colocalization of MARCO and CD68 using immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, bone marrow monocytes also contribute to maintain KC pool when Em-KCs are insufficient to maintain it ( 13 ). Studies have demonstrated that when Em-KCs are depleted by clodronate liposomes (CLs) ( 14 , 15 ), diphtheria toxin ( 4 ), anti-TIM4 antibody ( 6 ) or high dose irradiation ( 16 ), monocytes are recruited and differentiate into KCs to replenish the vacancy. In patients received liver transplant, recipient macrophages are also emerged in transplanted livers ( 17 ).…”
Section: Kc In Homeostasismentioning
confidence: 99%
“…But it should be noticed that these bone marrow monocyte-derived KCs (BM-KCs) are different from BMMs in injured liver. BM-KCs express KC markers (including CLEC4F, CLEC2, VSIG4, TIM4), while BMMs mainly highly express CCR2 and show no KC marker expressions ( 6 , 18 ).…”
Section: Kc In Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic macrophages play an important role in liver repair after acute liver injury, including hepatic I/R injury (2). Macrophage phenotype shift from a proinflammatory to a reparative phenotype in the inflammatory liver is crucial for liver repair following hepatic I/R injury (3)(4)(5)(6). However, the mechanisms by which the liver is repaired via macrophage differentiation remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%